Analysis of the Combination of the Soil Stability and the Slope Analysis Methods to Design a Retaining Wall on the Akoasa Mountain Mudslide (Accra, Ghana) - Min, Song Jian; Mayuka, Ruth Nzinga; Joseph, Annan Joseph; Cosmos, Boadu Cosmos; Samuel, Adombia Samuel; Qiaomin, Zhang Qiaomin (International Journal of Computing and Engineering, 2023)
Purpose: The most unsafe geological chance in steep places is landslides. Landslides in Ghana have long been a most important source of worry, mainly during the rainy season. In some highland settlements, most of the buildings in Kasoa are impacted because the community is situated on a landslide terrain. Methodology: In this project, cantilever and relieving platform retaining walls with varied heights of 3 to 10 meters and SBC 160 KN/m2 were analyzed and designed. Additionally, a comparative of factors like cost, efficiency, bending moment, stability against overturning, and sliding between the two retaining walls are shown. The cost comparison is done together with the comparative analysis, and the lowest or best estimate is selected. Findings: This research also demonstrated that the relieving platform retaining wall is less expensive, more stable, and relieves the heel portion's bending moment Unique Contributions to Theory, Policy and Practice: To reduce the risk of landslides on the road or in the town as a whole, we plan to construct or design a retaining wall model and, if possible, add a storm drainage system to the project.